MARKETING MIX DAN PENGARUHNYA TERHADAP KEPUTUSAN PEMBELIAN (STUDI EMPIRIK PADA PT. CENTRAL SAKTI MOTOR CABANG SURAKARTA) - Nendi Angraini (KELOLA, 2018)
The purpose of this study is to determine the effect of Marketing Mix on purchasing decisions at PT. Central Sakti Motor branch of Surakarta. The sample of this research is 100 respondents. Data analysis tools are: instrument test, classical assumption test, multiple linear regression analysis, t test, F test, R2 test. The result of analysis by using multiple linear regression equation shows the regression equation as follows: Y = 2,955 + 0,280X1 + 0,083 X2 + 0,131X3 + 0,185X4 + (- 0,081 X5) + 0,299X6 + 0,114X7. The result of t test shows that Product, Promotion, and Physical Evidence variable have positive and significant effect on Purchase Decision, while Price variable, Location, and Process have positive but not significant effect on Purchase Decision, and Person variable has negative and insignificant effect to Purchase Decision. F test results show together marketing mix variables have a significant effect on Purchase Decision. Coefficient Determination Test Results (R2) of Adjusted R Square value obtained results of 0.452 which means Purchasing Decision at PT. Central Sakti Motor Surakarta branch can be explained by 45% marketing mix variables, while the remaining 55% is explained by other variables outside the variables studied.Keywords: Marketing Mix and Purchase Decision.